The influence of service quality and trust on satisfaction of BPJS health outcoming patients in Islamic Hospital Karawang - Ina Ratnasari; Sri Sekar Sari; Kosasih Kosasih (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
This study aims to obtain empirical evidence and found the clarity of the phenomenon and concluded on Influence of Service Quality and trust on patient satisfaction of outpatient health BPJS at the Islamic Hospital Karawang. This thesis is expected to contribute to the development of science, especially the management, marketing management, service quality, trust and patient satisfaction. The study was conducted by using descriptive and verification methods, namely: collecting, presenting, analyzing, and testing hypotheses, and make their conclusions and suggestions. Samples were collected using Proportionate Stratified random sampling method with a sample size of 393 respondents from the population of 21.627 people. Data analysis technique used is the technique Scale Range Analysis and Path Analysis with the help Method of Successive Interval (MSI), the computer program Microsoft Excel 2013, and SPSS version 20. From the analysis of research data, obtained some conclusions as follows: Service Quality amounted to 1397,4 is at Agree criteria, Means service quality rated Good. Trust at 1427,6 is at Agree criteria, meaning the trust rated Good. Patient satisfaction of 1432,3,5 is at Agree criteria, meaning patient satisfaction in rated Good. There Correlation Between service quality by trust at 0,811. This shows that a very strong and direct Correlation because it has a positive value. There Effect of Partial Between service quality on patient satisfaction by 42,8% and there Between Partial Influence Trust toward patient satisfaction of 37,9%. There Simultaneous Effect Between Service Quality and Trust toward patient satisfaction of outpatient health BPJS at the Islamic Hospital Karawang amounted to 80,7%, while the rest are other factors not examined by 19,3%. From the description above, the suggestions given include improving the quality of service and providing trust to increase patient satisfaction.